IMPLEMENTASI KEBIJAKAN PENDIDIKAN KEJURUAN PADA KELAS JUNIOR (SMP) SEBAGAI UPAYA MENGATASI PENGANGGURAN - Andhika, Adi; Immanuel, Brenden F; Hafni; Fawzan, Rizki (LPPM, Universitas Negeri Jakarta, 2022)
Derived from the problem of unemployment that occurs in school and college graduates which is a problem in society. Therefore, we need a solution in the form of a policy that can maintain and improve the relationship of junior class schools with the wishes of work areas, business areas and industrial areas in the future. This article was created so that we can learn and understand the problem of unemployment and how to solve it, in this case the link and match policy can be a good solution for education in tackling problems such as unemployment in the future. The results of the discussion of this article are expected to provide a broad view of the implications of vocational education policies for the junior class in increasing their career potential and expertise from an early age so that in the future they will overcome unemployment, in this case what skills or careers will be required in the work area and what skills. the most attractive desired work area in the future.